A method for preparing nanocomposite - Mohamad, Rosfarizan; Namvar, Farideh; Abdul Rahim, Raha; Azizi, Susan; Rahman, Heshu Sulaiman (2014)
The present invention relates to a method for preparing nanocomposite. The method for preparing hyaluronan/Sargassum muticum/zinc oxide nanocomposite comprises of providing a seaweed extract; stirring the seaweed extract with zinc precursor solution and hyaluronan solution to form the nanocomposite; purifying the nanocomposite; and adjusting pH of the nanocomposite to physiological pH. The nanocomposite is used for biomedical and cosmetical application. The method is simple and easy to conduct.